USE OF VIDEO COMMUNICATION TECHNOLOGIES TO SUPPORT RESEARCH ACTIVITIES OF SCIENTISTS AND SCIENTIFIC AND PEDAGOGICAL WORKERS - Tkachenko, Віталій (Journal of Information Technologies in Education (ITE), 2021)
The paper reviews and analyzes the domestic and foreign experience of using video communication technologies for carrying out scientific researches. It was determined, that video telephony is usually used for communication, holding session, solving organization problems; video broadcasting is used for distance education; videoconference is used for scientific and practical activities, work at a distance of scientific groups, working groups. The main components of the general model of the implementation of video communication technologies such as a WEB-oriented video conferencing system are singled out, that based on the analysis of foreign and domestic experience regarding the use of video communication technologies to support the research activities of scientific and pedagogical workers. The main components of research activity of scientific and scientific and pedagogical workers, which need support of video communication technologies are determined there, namely: scientific-pedagogical, scientific-organizational, scientific-technical, experimental. It was revealed that foreign researchers focus on video communication technologies, in particular videoconferences, which provide significant support to the research activities of scientific and pedagogical workers. Examples of using cloud computing for organizing and conducting videoconferences are given there. The author's vision of the general model of the implementation of video communication technologies, as a WEB-oriented video conferencing system, and the general model of the implementation of the terminal complex of the user of the video-communications technologies, as WEB-oriented video conferencing system, is presented. The main components of the WEB-oriented video conferencing system are distinguished: terminal user modules and electronic communications system. The concept of videoconference, video telephony, video-broadcasting as the technologies of video communications, which can be used to support the research activities of scientific and scientific-pedagogical workers, is defined in the paper.